Detecting anxiety and depression in general medical settings. - Goldberg, D. (1988)
To aid general practitioners and other non-psychiatrists in the better recognition of mental illness short scales measuring anxiety and depression were derived by latent trait analysis from a standardised psychiatric research interview. Designed to be used by non-psychiatrists, they provide dimensional measures of the severity of each disorder. The full set of nine questions need to be administered only if there are positive answers to the first four. When assessed against the full set of 60 questions contained in the psychiatric assessment schedule they had a specificity of 91% and a sensitivity of 86%. The scales would be used by non-psychiatrists in clinical investigations and possibly also by medical students to familiarise them with the common forms of psychiatric illness, which are often unrecognised in general medical settings.